Differences between sprint tests under laboratory and actual cycling conditions - Bertucci, W.; Taiar, R.; Grappe, F. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aim of this study was to compare the maximal power output (POpeak) and force-velocity relationships in sprint cycling obtained from a laboratory protocol and from a field test during actual cycling locomotion. Methods: Seven male competitive cyclists performed 6 sprints (3 in the seated position and 3 in the standing position) on an ergo-trainer (Tacx, Netherlands) and 6 sprints during actual cycling locomotion in a gymnasium. The bicycle was equipped with the SRM Training System (Schoberer Rad Messtechnik, Germany) to measure (200 Hz) the power output (PO, W), the pedalling cadence (rpm), and the velocity (km·h-1). From these measurements, the maximal force on the pedal (Fmax), the theoretical maximal force (Fo, N) and the theoretical maximal pedalling cadence (V0, rpm) were determined. During each sprint test the lateral bicycle oscillations were measured from a video analysis. Results: During standing and seated sprints in the gymnasium, Fo and Fmax were significantly higher (p<0.05) compared with sprints on the ergo-trainer (+12% and +32%, respectively). The POpeak during sprints in seated and standing positions in the gymnasium was significantly (p<0.05) lower (-4%) and higher (+6%) respectively, compared with the ergo-trainer. For standing position in the gymnasium the kinematics analysis indicated a 24° mean lateral bicycle oscillation compared with 0° on the ergo trainer. Conclusion: The results of this study indicate that POpeak, Fo, and time to obtain POpeak were different between laboratory and actual cycling conditions. To obtain a valid estimation of the maximal power output, it is necessary to perform sprint tests during actual cycling locomotion. Thus, in the laboratory, it is advisable to use a cycle ergometer that enables natural lateral oscillations.